A PROMOÇÃO DE VENDAS E A CRIANÇA: O PEQUENO CONSUMIDOR LEVADO A SÉRIO NO PONTO DE VENDA - Gil, Rosana de Araujo (2004)
This paper discusses the growing importance of the infantile-consumer segment in the market, focusing in the point of purchase (POP) and the procedures to be implemented in order to attract this type of consumer. This study is based on the conceptual framework of retailing and Brazilian s market trends, ending with a research on parents and kids at the point of purchase (POP).